Optimization of Crude Palm Oil Distribution Costs in PT. Perkebunan Nusantara III Using Vogel's Approximation Method, Russel Approximation Method and Stepping Stone Method - Nadya Pratiwi; Siregar, Rosman (Journal of Mathematics Technology and Education, 2021)
PT. Perkebunan Nusantara III is an Indonesian State-Owned Enterprise engaged in oil palm and rubber plantations. The company is headquartered in Medan, North Sumatra. In general, the distribution process of CPO is one of the most important aspects to be planned, because it will greatly affect the overall cost efficiency of the project. The increase in project costs is often caused by a CPO distribution process that is not optimal. The method used to solve the distribution optimization problem is Vogel's Approximation Method and Russell's Approximation Method to determine the initial solution and optimization test using the Stepping Stone method. From the results of the calculation of the Vogel's Approximation Method method for the initial completion and continued by using the Stepping Stone Method is the method that gives optimal results. For the final settlement, a minimum fee of Rp. 34,417.014,501.